Bacterial Pathogens and Antimicrobial Resistance Patterns in Pediatric Urinary Tract Infections: A Four-Year Surveillance Study (2009–2012) - Seyed Reza Mirsoleymani; Morteza Salimi; Masoud Shareghi Brojeni; Masoud Ranjbar; Mojtaba Mehtarpoor (International Journal of Pediatrics)
The aims of this study were to assess the common bacterial microorganisms causing UTI and their antimicrobial resistance patterns in Bandar Abbas (Southern Iran) during a four-year period. In this retrospective study, samples with a colony count of ≥105 CFU/mL bacteria were considered positive; for these samples, the bacteria were identified, and the profile of antibiotic susceptibility was characterized. From the 19223 samples analyzed, 1513 (7.87%) were positive for bacterial infection. UTI was more frequent in male (54.9%). E. coli was reported the most common etiological agent of UTI (65.2%), followed by Klebsiella spp. (26%), Pseudomonas aeruginosa (3.6%), and Staphylococcus coagulase positive (3.7%). Results of antimicrobial susceptibility analysis for E. coli to commonly used antibiotics are as follows: Amikacin (79.7%), Ofloxacin (78.3%), Gentamicin (71.6%), Ceftriaxone (41.8), Cefotaxime (41.4%), and Cefixime (27.8%). Empirical antibiotic selection should be based on awareness of the local prevalence of bacterial organisms and antibiotic sensitivities rather than on universal or even national guidelines. In this study, Amikacin and Gentamicin were shown to be the most appropriate antibiotics for empiric therapy of pyelonephritis, but empirical therapy should only be done by specialist physicians in cases where it is necessary while considering sex and age of children.